The role of carbohydrate malabsorption syndrome in the pathogenesis of rotavirus diarrhea (a literature review) - Usachova, O. V.; Vorobiova, N. V.; Silina, E. A.; Matvieieva, T. B.; Усачова, Олена Віталіївна; Воробйова, Наталія Володимирівна; Сіліна, Єлизавета Андріївна; Матвєєва, Т. Б. (Запорізький державний медико-фармацевтичний університет, 2024)
The aim – to summarize literature data on the pathogenetic mechanisms of the diarrheal syndrome development in children with rotavirus infection and to determine the role of carbohydrate malabsorption syndrome in it through a complex analysis of literature reviews and empirical studies. Rotavirus infection (RVI) remains the main cause of severe dehydrating gastroenteritis in children under five years of age. One of the most important pathogenetic links of rotavirus gastroenteritis is the development of osmotic diarrhea induced by carbohydrate malabsorption syndrome. Its development is associated with disaccharidase insufficiency and impaired absorption of monosaccharides in the small intestine. Carbohydrate malabsorption syndrome is found in 67.0–98.3 % of children with RVI. Its laboratory manifestations (an increase in levels of fecal carbohydrates and lactose) are observed starting from the first days of the disease, and the maximum indicators are recorded in the period from the fifth to the seventh day. Conclusions. Carbohydrate malabsorption syndrome is observed in the absolute majority of children with RVI, and its maximum severity is noted from the fifth to the seventh day of the disease, being realized mainly due to lactase deficiency. The severity of carbohydrate malabsorption syndrome can be influenced by concomitant pathological conditions, that lead to a decrease in the activity of disaccharidases in the small intestine, and the metabolic activity of the intestinal microbiota. Мета роботи – узагальнити відомості щодо патогенетичних механізмів розвитку діарейного синдрому при ротавірусній інфекції у дітей та визначити роль у ньому синдрому мальабсорбції вуглеводів шляхом комплексного аналізу оглядів фахової літератури й емпіричних досліджень. Ротавірусна інфекція (РВІ) залишається основною причиною тяжких дегідратуючих гастроентеритів у дітей віком до п’яти років. Одна з найважливіших патогенетичних ланок ротавірусного гастроентериту – розвиток осмотичної діареї, що спричинена синдромом мальабсорбції вуглеводів. Його розвиток пов’язаний із дицукридазною недостатністю та порушенням абсорбції моноцукридів у тонкому кишечнику. Синдром мальабсорбції вуглеводів виявляють у 67,0–98,3 % дітей із РВІ. Його лабораторні прояви (підвищення рівня вуглеводів і лактози у фекаліях) визначають, починаючи з перших днів хвороби, а максимальні показники фіксують у період від п’ятої до сьомої доби. Висновки. Синдром мальабсорбції вуглеводів визначають в абсолютної більшості дітей із РВІ, він досягає максимальної виразності з п’ятої до сьомої доби хвороби та реалізується передусім шляхом лактазної недостатності. На виразність синдрому мальабсорбції вуглеводів можуть впливати супутні патологічні стани, що призводять до зниження активності дицукридаз у тонкому кишечнику, та метаболічна активність кишкової мікробіоти.
Місце синдрому мальабсорбції вуглеводів у патогенезі ротавірусної діареї (огляд літератури)
Usachova O. V. - ORCID ID: 0000-0003-0250-1223; Vorobiova N. V. - ORCID ID: 0000-0001-7610-8067; Silina E. A. - ORCID ID: 0000-0002-3199-9297.
Keywords: rotavirus infection; pathogenesis; diarrhea; carbohydrate malabsorption syndrome; lactase deficiency; children; ротавірусна інфекція; патогенез; діарея; синдром мальабсорбції вуглеводів; лактазна недостатність; діти